Legal Protection for Gig Workers in the Digital Economy: A Critical Review of Labor Relations in Indonesia - Wibowo, Sundaru Guntur; Susanto, Fredy (Eastasouth Institute, 2025)
The rapid growth of the digital economy in Indonesia has given rise to gig work arrangements, characterized by short-term, task-based employment facilitated through online platforms. While offering flexibility and new income opportunities, gig work often operates outside the scope of traditional labor laws, leaving workers without adequate legal protection. This study employs a normative legal analysis to critically review Indonesia’s industrial relations framework in addressing the rights and obligations of gig workers. The research examines relevant national legislation, judicial decisions, and comparative legal approaches from other jurisdictions, alongside international labor standards. Findings reveal that the current legal framework is insufficient to address the unique characteristics of platform-mediated work, resulting in legal uncertainty over employment classification, limited access to social protection, and weak collective bargaining rights. Drawing from comparative models and ILO conventions, the study recommends legal reforms to define gig work, introduce hybrid employment categories, extend mandatory social protection coverage, recognize gig worker associations, and establish specialized dispute resolution mechanisms. These measures are essential for balancing labor protection with the flexibility and innovation of the digital economy in Indonesia.